2005
DOI: 10.1080/00365590500220230
|View full text |Cite
|
Sign up to set email alerts
|

Subcapsular versus total orchiectomy in the treatment of advanced prostate cancer: A randomized trial

Abstract: Subcapsular orchiectomy is associated with significantly fewer postoperative complications than total orchiectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…In their study of 74 patients, Zhang et al (7) reported complications rates of 3% and 22% respectively for patients undergoing subcapsular and total orchiectomy, and similar rates have been confirmed in numerous other studies (8,9). These studies have generally shown that the subcapsular technique has fewer complications.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In their study of 74 patients, Zhang et al (7) reported complications rates of 3% and 22% respectively for patients undergoing subcapsular and total orchiectomy, and similar rates have been confirmed in numerous other studies (8,9). These studies have generally shown that the subcapsular technique has fewer complications.…”
Section: Discussionsupporting
confidence: 57%
“…A notable finding of our study was the short surgery times in patients undergoing subcapsular orchiectomy, which was not consistent with the literature. Roosen et al (8) reported that the subcapsular technique took significantly longer to perform. We attribute this discrepancy to our variation on the surgical technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is either performed as total or subcapsular techniques. In a comparison of the two techniques Roosen and colleagues (Roosen et al, 2005) noted that subcapsular orchiectomy is associated with significantly fewer postoperative complications than total orchidectomy. Desmond and colleagues (Desmond et al, 1988) operated on 100 patients with carcinoma of the prostate by bilateral subcapsular orchidectomy under local anesthesia over a 5-year period.…”
Section: Testicular Biopsy Orchidopexy and Orchidectomymentioning
confidence: 99%